1993
DOI: 10.1111/j.1151-2916.1993.tb07762.x
|View full text |Cite
|
Sign up to set email alerts
|

Drying of Granular Ceramic Films: I, Effect of Processing Variables on Cracking Behavior

Abstract: Drying of binder-free granular ceramic films was studied to identify processing variables which affect their cracking behavior. Films were prepared from electrostatically stabilized suspensions of a-alumina in water. A critical cracking thickness (CCT) was determined, above which films would spontaneously crack during drying. The effects of particle size, liquid surface tension, drying rate, dispersion stability, and sedimentation time were evaluated by a statistical design methodology. The CCT for films prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
203
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(220 citation statements)
references
References 10 publications
11
203
1
2
Order By: Relevance
“…11). These changes were expressed as drying fronts, which propagated across the film at some speed v, as have been previously reported [3, 4,12,30,31]. Observing at one point, the transitions were seen as occurring at different times, as the fronts successively passed through the beam.…”
Section: Discussion Three Transitionsmentioning
confidence: 99%
“…11). These changes were expressed as drying fronts, which propagated across the film at some speed v, as have been previously reported [3, 4,12,30,31]. Observing at one point, the transitions were seen as occurring at different times, as the fronts successively passed through the beam.…”
Section: Discussion Three Transitionsmentioning
confidence: 99%
“…This was originally demonstrated through a series of centrifuge experiments, which showed that this critical pressure corresponded to the maximum pressure that could be generated by the repulsive interactions between adjacent colloidal particles [9][10][11]. The connection of aggregation to drying was then made by Chiu et al, who argued that drying colloidal alumina will solidify only after the repulsive interactions between particles were overcome by capillary forces [3], and by Dufresne et al, who also noted the presence of such an aggregation front in drying ludox [6]. The work of Tsapis et al has further demonstrated the existence of a fluid-to-solid transition in evaporating colloidal droplets, at a fixed aggregation pressure, when the capillary forces balanced the electrostatic repulsion of adjacent particles [12].…”
Section: Introductionmentioning
confidence: 99%
“…The appearance of three distinct fronts have frequently been reported, which represent solidification, cracking, and pore opening (e.g. [3][4][5][6][7][8]). For films that are dried below their critical film thickness, the fracture front is absent, and the film dries without breaking [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently the thickness at the trace edge is higher than the trace centre. From the literature, crack formations have been reported to occur for thicker films [40] and films which are above a certain critical thickness [41,42]. When the silver overprint was increased to 2 layers, a wider crack area was observed for the smaller traces (100 µm and 500 µm), while the cracks for the 1 mm trace remained at the edges (Figure 3(B)).…”
Section: Cracking In Silver Traces On Emd 6200mentioning
confidence: 95%